Learning Islamic Religious Education Through Contextual Learning Models: Islamic Moderation Studies - Nurdalia (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The purpose of this project is to find out how contextual model learning can be used to teach moderate Islam. Islamic education is a collection of coordinated activities designed to get students excited and ready to learn in accordance with the learning objectives. Teachers of Islamic education must use model learning that is designed to maximize the potential held by participating educators to correctly achieve objective learning. A contextual learning methodology can assist students in integrating Islamic moderation values, which is one of the learning objectives of Islamic education. Using a qualitative methodology, this inquiry was conducted. Researchers should be able to understand, observe, and perform studies regarding in-depth Islamic moderation learning through contextual model learning more correctly with the use of a qualitative technique. The study's findings suggest that: 1) Implementing Islamic education can improve students' cognitive comprehension of Islamic moderation principles. 2) Implementing Islamic education can improve students' affective features to understand moderation in Islam by using contextual learning methods. 3) By using contextual learning techniques in Islamic education, students can absorb moderate Islamic views.